2012
DOI: 10.1371/journal.ppat.1002566
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma Herpesvirus Upregulates Aurora A Expression to Promote p53 Phosphorylation and Ubiquitylation

Abstract: Aberrant expression of Aurora A kinase has been frequently implicated in many cancers and contributes to chromosome instability and phosphorylation-mediated ubiquitylation and degradation of p53 for tumorigenesis. Previous studies showed that p53 is degraded by Kaposi's sarcoma herpesvirus (KSHV) encoded latency-associated nuclear antigen (LANA) through its SOCS-box (suppressor of cytokine signaling, LANASOCS) motif-mediated recruitment of the EC5S ubiquitin complex. Here we demonstrate that Aurora A transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 52 publications
(59 reference statements)
4
49
0
Order By: Relevance
“…While deregulation of AK-B has earlier been shown to be associated with many human cancers, the functional role for AK-B in EBV-mediated human cancers has not been extensively explained. Recently, a study from our lab showed that the Aurora kinase A (AK-A), the first member of the AK family, was functionally regulated by the latency-associated nuclear antigen (LANA) in Kaposi's sarcoma-associated herpesvirus (KSHV)-associated viral oncogenesis (27). However, a role for the other AK-B family members in gammaherpesvirus-infected cells remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While deregulation of AK-B has earlier been shown to be associated with many human cancers, the functional role for AK-B in EBV-mediated human cancers has not been extensively explained. Recently, a study from our lab showed that the Aurora kinase A (AK-A), the first member of the AK family, was functionally regulated by the latency-associated nuclear antigen (LANA) in Kaposi's sarcoma-associated herpesvirus (KSHV)-associated viral oncogenesis (27). However, a role for the other AK-B family members in gammaherpesvirus-infected cells remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The CFAR Immunology Core maintains an Institutional Review Board (IRB)-approved protocol in which Declaration of Helsinki protocols are strictly followed. Every donor gave written and informed consent at the CFAR Immunology Core (27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also latency-associated nuclear antigen (LANA) forms complexes with p53 in the nuclei of latently infected cells (84) and induces p53 ubiquitination and degradation (85,86). Moreover, LANA markedly elevates the expression of Aurora A oncogenic kinase, which leads to phosphorylation of p53 at S215 and S315 and subsequent p53 ubiquitination and proteasome-mediated degradation (87). Thus, KSHV developed…”
Section: Discussionmentioning
confidence: 99%